A revision of the Elachista dispilella complex (Lepidoptera: Gelechioidea: Elachistidae) - Kaila, Lauri; Baran, Tomasz; Mutanen, Marko (Zootaxa, 2015)
The Elachista dispilella group and its subordinate E. dispilella species complex are characterized. Identity of the long confused oldest names applicable for taxa in the E. dispilella complex, i.e., E. dispilella Zeller, E. festucicolella Zeller, and E. distigmatella Frey, is resolved. Elachista dispilella Zeller is the valid name for the species often identified as E. festucicolella, E. steueri Traugott-Olsen, or E. manni Traugott-Olsen. Elachista distigmatella Frey is the valid name for the species regularly identified as E. dispilella. The identity of E. festucicolella Zeller, so far entirely dubious, is clarified. Nineteen species attributable to the E. dispilella complex sensu Traugott-Olsen are recognized. The following new synonymies are proposed: Elachista steueri Traugott-Olsen, 1990, syn. nov.; E. manni Traugott-Olsen, 1990, syn. nov.; E. jaeckhi Traugot-Olsen, 1990, syn. nov.; and E. gebzeensis Traugott-Olsen, 1990, syn. nov., are considered synonyms of E. dispilella Zeller, 1839. Elachista klimeschiella Parenti, 2002 is synonymized with E. festucicolella Zeller, 1853; and Elachista purella Sruoga, 2000 with E. levasi Sruoga, 1998, syn. nov. Identification keys for males and females are provided. All species are diagnosed, the lesser known are also redescribed. Four new species are described: Elachista implana Kaila, sp. nov., from Austria; E. ripai Kaila, sp. nov., from Kyrgyzstan; Elachista sitibunda Kaila, sp. nov., from Uzbekistan; and Elachista laterotis Kaila, sp. nov., from Turkey.